Brand Making Process in B2B Companies (Case Study: Tam Iran Khodro Company) - Nasr, Mahmoud Samiei; Mahmoudzadeh, Mohsen; Mousavi, Shahab; Alikhani, Elham Agha (Asian Accounting and Auditing Advancement, 2016)
In this research, we have tried to analyze the brand-making process of Tam Iran Khodro Company from the viewpoint of the employees who are the most important factor in the brand-making of a company. The purpose of this research is to know whether such companies not directly connected with the final customers will try to be changed into a valid brand from a mere trade name. Also, another purpose of this stage is to provide a general and up-to-date picture of internal company-based perceptions of the brand, so that the process will be started based on the business realities. This research was carried out by holding the training courses for all employees in regards to the upcoming challenges at the time of entering the brand-making management and distributing questionnaires which are the most important instruments of this research. The present research is a field study research from the viewpoint of the manner of gathering information, a survey study research from the viewpoint of the manner of performance, and developmental & applied research from the viewpoint of the purpose. The statistical universe of this research consists of personnel of Tam Iran Khodro Company including managers and employees who are a total of 450 persons and 126 persons out of which were selected accidentally as the final sample. The instrument for gathering information is a questionnaire designated by the researchers. Cronbach’s alpha coefficient of this questionnaire was calculated at 0.838 considering 15 persons as the initial sample and since this digit is more than 0.7, its reliability is proved. Student’s t-tests & Friedman test were used to test the hypotheses. The results indicate that the Tam Iran Khodro brand has no favorable conditions. Finally, occupational stability, promises of Tam Iran Khodro Company to the customers, motivation of the employees, and its role in the improvement of Tam Iran Khodro Brand and capabilities of Tam Iran Khodro Brand, respectively, were determined as effective factors for Tam Iran Khodro Brand from the viewpoint of the employees.